(untitled) (NTU journal for Administrative and Human Sciences (JAHS), 2025)
Information and communication technology (ICT) has a significant impact on all economic sectors through innovation, higher productivity, and economic growth. This research paper seeks to illustrate how specific ICT indicators have influenced the gross domestic product (GDP) of selected Arab nations (Iraq, Jordan, the United Arab Emirates, Saudi Arabia and Morocco) during the period from 2007 to 2021.. The multiple regression model has been used and implemented by Python language. The obtained results demonstrate that the effect of fixed telephone line subscriptions adversely affects the Gross Domestic Product (GDP) in the prementioned countries , while the international bandwidth of the Internet and the Internet Users Index positively affect the GDP in the countries of Saudi Arabia, Jorden and the United Arab Emirates. On the other hand, Morocco was the opposite.